SILICON AS A BIOSTIMULANT IN CUCUMBER CULTIVATION (Cucumis sativus L.)] - Juan José Reyes Pérez; Luis Tarquino Llerena Ramos; Juan Antonio Torres Rodriguez; Luis Guillermo Hernández Montiel; Ramón Klever Macias Pettao; Erendira Aragón Sánchez; Alejandro Palacios (Tropical and Subtropical Agroecosystems)
Background. The use of silicon as a fertilizer can reduce the need to use chemical fertilizers and thereby prevent the adverse effects of the latter. Objective. To evaluate silicon as a biostimulant in the cultivation of cucumber (Cucumis sativus L.) under greenhouse conditions. Methodology. Four concentrations of silicon dioxide (0, 0.15, 0.21 and 0.27 g of SiO2 per plant) were applied to the plant at six, 20 and 28 d after transplanting (six days after the emergency). At 40 days after sowing, the length of guides (m), stem diameter (mm) and number of leaves were determined. Likewise, the number of flowers, number of fruits, length fruits, diameter and weight of the fruit and yield (kg ha-1). The variables were analyzed using a general linear model and polynomials by regression. Results. The treatment of 0.22 g of SiO2 per plant increased stem diameter and length of the guides. The concentration of 0.27 g of SiO2 per plant had a positive influenced the growth of the cucumber crop, allowing fruit harvests of greater length, weight and diameter and a greater number of fruits per plant. Implications. It is possible to increase the yield of cucumber crops by applying silicon. Conclusions. The use of SiO2 at concentrations of 0.27 g per cucumber plant under greenhouse conditions increases it yield per hectare.